Giant magnetocaloric effect in Gd2NiMnO6 and Gd2CoMnO6 ferromagnetic insulators. (10th August 2015) - Krishna Murthy, J; Devi Chandrasekhar, K; Mahana, Sudipta; Topwal, D; Venimadhav, A
Abstract: We have investigated the magnetocaloric effect in double perovskite Gd2 NiMnO6 (GNMO) and Gd2 CoMnO6 (GCMO) samples by magnetic and heat capacity measurements. Ferromagnetic ordering is observed at ~130 K (~ 112 K) in GNMO (GCMO), while the Gd exchange interactions seem to dominate for T   <  20 K. In GCMO, below 50 K, antiferromagnetic behaviour due to the 3d–4f negative exchange interaction is observed. A maximum entropy (−Δ S M ) and adiabatic temperature change of ~35.5 J Kg −1  K −1 (~ 24 J Kg −1  K −1 ) and 10.5 K (6.5 K) is observed in GNMO (GCMO) for a magnetic field change of 7 T at low temperatures. Absence of magnetic and thermal hysteresis and their insulating nature make them promising for low temperature magnetic refrigeration.